The certain Coups and the Handling of Uncertainty: Challenges to the Ideology of Populism and Elections - Samnieng, Chaipong (Journal of Social Sciences, Chiang Mai University, 2023)
The uncertainty of Thai politics explicitly emerged after the Black May event in 1992, and continued towards the economic crisis of 1997, leading to the consistent political unpredictability in the last twenty years (1997-2017). This uncertainty in politics shows an increasing strategic direction of the undemocratic transformative process. The adage “certain coups and the handling of uncertainty” encapsulates the relationship between coup certainty and strategic political uncertainty. This adage implies that the coups have been devised by the Thai ruling class to create social orders in politics, and to control the uncertainty of the pro-democracy movements, with the aim to maintain the powers of the elite class. This reflects the power relations under the concepts of network monarchy and the deep state. However, the studies that used these two concepts do not succeed in explaining the uncontrollable voids, or unmanageable uncertainties, such as elections. The election in Thailand has become the area of crucial reprisal by both authoritative and democratic allies to attempt to handle the emerging uncertainties. Yet, Thai political studies have so far investigated the phenomena by using the concept of uncertainty at only a limited level i.e. most of the research considered the uncertainty from the economic perspective. Meanwhile, the politics of uncertainty through voting renders conditions of different voting systems in each country. The election is turned into a tactical tool in an overarching strategy enabling the ruling class to legitimize the power to change the regime, whilst concurrently maintaining the deliberate uncertainty. Therefore, the adoption of the uncertainly concept helps to more broadly and comprehensively understand of the dynamics in Thai politics.